Enhanced helium exhaust during edge-localized mode suppression by resonant magnetic perturbations at DIII-D. (6th April 2020) - Hinson, E.T.; Schmitz, O.; Abrams, T.; Briesemeister, A.; Bykov, I.; Chrystal, C.; Collins, C.; Evans, T.E.; Frerichs, H.; Grierson, B.A.; Moyer, R.A.; Paz-Soldan, C.; et al.
Abstract: Effective helium confinement time, τ p *, He, and its ratio with energy confinement time, τ p *, He / τ E, are key metrics quantifying the suitability of fusion plasmas for a continuous burn. Comparisons in the DIII-D tokamak of discharges with suppression of edge localized modes (ELMs) by resonant magnetic field perturbations (RMPs) to the corresponding unperturbed ELMy discharges found that both of these metrics were strongly reduced, by a factor of approximately 2, after application of the RMPs. This reduction in τ p *, He during RMP ELM suppression was observed in the plasma core, edge, and pumping plenum, where higher neutral helium concentration during RMPs was also measured. These findings provide evidence that future devices employing RMP ELM suppression may meet or even exceed the helium exhaust provided by the ELMs themselves, reducing helium ash, and thus maintaining high fusion gain.